Obesity, diabetes, coffee, tea, and cannabis use alter risk for alcohol-related cirrhosis in 2 large cohorts of high-risk drinkers - Whitfield, John B.; Masson, Steven; Liangpunsakul, Suthat; Mueller, Sebastian; Aithal, Guruprasad P.; Eyer, Florian; Gleeson, Dermot; Thompson, Andrew; Stickel, Felix; Soyka, Michael; Muellhaupt, Beat; Daly, Ann K.; et al. (The American journal of gastroenterology, 2021)
INTRODUCTION: - Sustained high alcohol intake is necessary but not sufficient to produce alcohol-related cirrhosis. Identification of risk factors, apart from lifetime alcohol exposure, would assist in discovery of mechanisms and prediction of risk. - METHODS: - We conducted a multicenter case-control study (GenomALC) comparing 1,293 cases (with alcohol-related cirrhosis, 75.6% male) and 754 controls (with equivalent alcohol exposure but no evidence of liver disease, 73.6% male). Information confirming or excluding cirrhosis, and on alcohol intake and other potential risk factors, was obtained from clinical records and by interview. Case-control differences in risk factors discovered in the GenomALC participants were validated using similar data from 407 cases and 6,573 controls from UK Biobank. - RESULTS: - The GenomALC case and control groups reported similar lifetime alcohol intake (1,374 vs 1,412 kg). Cases had a higher prevalence of diabetes (20.5% (262/1,288) vs 6.5% (48/734), P = 2.27 × 10−18) and higher premorbid body mass index (26.37 ± 0.16 kg/m2) than controls (24.44 ± 0.18 kg/m2, P = 5.77 × 10−15). Controls were significantly more likely to have been wine drinkers, coffee drinkers, smokers, and cannabis users than cases. Cases reported a higher proportion of parents who died of liver disease than controls (odds ratio 2.25 95% confidence interval 1.55-3.26). Data from UK Biobank confirmed these findings for diabetes, body mass index, proportion of alcohol as wine, and coffee consumption. - DISCUSSION: - If these relationships are causal, measures such as weight loss, intensive treatment of diabetes or prediabetic states, and coffee consumption should reduce the risk of alcohol-related cirrhosis.
Publikationsdatum online: August 31, 2020
Gesehen am 07.05.2022